An optimized luciferin formulation for NanoLuc-based in vivo bioluminescence imaging - Chao Gao; Yan Wu; Connor Fitzgerald; Hui Wang; Tim Ugo; Tetsuo Uyeda; Wenhui Zhou; Yichi Su; Thomas A. Kirkland; Michael Z. Lin (Scientific Reports)
Abstract Bioluminescence imaging (BLI) is widely used in preclinical biomedical research for noninvasive tracking of cell populations and biochemical events in vivo. With recent improvements in BLI brightness from the engineering of bioluminescent enzymes (luciferases) and substrates (luciferins), optimizing luciferin formulations to maximize delivery and minimize toxicity becomes important, especially for marine coelenterazine-type luciferins with limited solubility. Here, we complete the characterization of a previously reported NanoLuc substrate, designated cephalofurimazine-9 (CFz9), and optimize its formulation with water-soluble excipients. We report a pH-controlled formulation of CFz9 enabling high-dose delivery to achieve peak brightness comparable to other furimazine analogs both inside and outside the brain while reducing toxicity. Thus, an optimized CFz9 formulation improves the performance and tolerability of whole-animal BLI with NanoLuc-based reporters.